Análise do modelo de valoração econômica dos impactos ambientais em acidentes: métodos aplicáveis aos acidentes ocorridos na região sudeste (2006-2012) - Miquelito, Alair do Carmo (2013)
The present study aims to analyze the model of economic valuation of environmental impacts in accidents occurring in southeastern Brazil, from 2006 to 2012. It is known that in spite of environmental assets do not have a market price, these have economic value, given their availability alters the level of production and welfare of society. Accordingly, the occurrence of environmental accidents with adverse environmental and economic reflection , people or companies that promoted these impacts, respond objectively the damage occurred, enforcing thus the central premise of the Polluter Pays Principle (constitutional legislation) that imposes the obligation to meet the costs and values a polluter should pay, if any environmental damage from its activities. Among the methods or techniques, of environmental valuation, and analyzed for environmental impacts, one can cite: Contingent Valuation, Travel Cost, Hedonic Price, Dose-Response, Replacement Costs and Avoided Costs. To achieve the proposed objective, we carried out a literature review , supported by a literature search in various literary sources, as well as documentary research reports IBAMA, and conducted searches in electronic databases such as journal portal CAPES. As a result of research industrial accidents (transport of hazardous materials and oil industry) were chosen in the southeastern region in the years 2006 to 2012 and performed critical analysis of the application of the methods and techniques used for environmental valuation in these cases. It was found that there is compatibility between the environmental impact and environmental valuation methods, however, the choice of the specific method will depend on the environmental impact of the characteristics of each case, as well as a revision of previous studies which are adapted to the case analyzed